Unrealistic expectations: Americans and international radio in cold war East Asia, 1951-75 - Meloni, Roberta (My University, 2025)
This dissertation examines four Cold War international radio initiatives that enhanced American economic influence and cultural power in East Asia to bolster the U.S. fight against communism from 1951 to 1975. It does so by focusing on Radio Free Asia (1951-53), Radio of Free Asia (1966-1975), the American Forces Vietnam Network (1962-1975), and Radio First Termer (1971). Altogether, these radio initiatives offer insight into how various American and Korean actors, including CIA officials and U.S. policymakers, the Unification Movement and South Korean President Park Chung Hee, the U.S. military authority and American soldiers in Vietnam, approached radio during two defining conflicts of the Cold War era: The Korean and Vietnam Wars. However, all four initiatives explored in this account failed to achieve their original intent or resulted in unintended consequences because the actors involved did not fully understand or master the complexity of the contexts in which their radio initiatives operated. Blinded by their self-serving interests and unrealistic expectations, they repeatedly oversimplified and misread the several contexts into which their initiatives were situated.
Keywords: United States; Americans; Broadcasting; International radio; East Asia; Cold war